2020
DOI: 10.3310/hsdr08150
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of ‘clinically unnecessary’ use of emergency and urgent care: the DEUCE mixed-methods study

Abstract: Background There is widespread concern about the pressure on emergency and urgent services in the UK, particularly emergency ambulances, emergency departments and same-day general practitioner appointments. A mismatch between supply and demand has led to interest in what can be termed ‘clinically unnecessary’ use of services. This is defined by the research team in this study as ‘patients attending services with problems that are classified as suitable for treatment by a lower urgency service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 128 publications
3
21
0
Order By: Relevance
“… 19 O'Cathain et al suggest that clinically unnecessary ED visits in children are sometimes caused by parents’ fear of the consequences of failing to bring their child to ED. 17 The countervailing risk of SARS-CoV-2 infection may have acted to offset this tendency, reducing the level of clinically unnecessary ED visits in children. We note however that all-age attendances where no clinical problem was detected, reduced and subsequently increased at a very similar rate to ED attendances as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 O'Cathain et al suggest that clinically unnecessary ED visits in children are sometimes caused by parents’ fear of the consequences of failing to bring their child to ED. 17 The countervailing risk of SARS-CoV-2 infection may have acted to offset this tendency, reducing the level of clinically unnecessary ED visits in children. We note however that all-age attendances where no clinical problem was detected, reduced and subsequently increased at a very similar rate to ED attendances as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…The first considers that patient decisions to attend ED which are influenced by three factors (i) symptom-related drivers such as anxiety and pain (ii) patient-related drivers such as coping capacity and feeling responsible for another's health and (iii) service-related drivers such as prior experience of ED, and availability of GP services. 17 The second framework classifies the factors that influence reductions in healthcare activity over the lockdown period: (i) the impact of policy choices (ii) changes in patient behaviour (iii) changes in the levels and types of morbidity. 18 The first framework is generic and longstanding, the second adds the COVID-19-pandemic context.…”
Section: Methodsmentioning
confidence: 99%
“…While interview participants across all groups were strongly influenced by concern over the seriousness of symptoms and a desire for reassurance, our survey found those in the 18‐24 age group were likely to feel less confident in deciding when to go to a doctor with a health problem, and to worry that pain indicated a serious problem. 24 Additionally, those aged 18‐44 were more likely to feel overwhelmed when they had an unexpected health problem. 24 These data echo Turnbull et al's findings that young adults more frequently identified themselves as anxious and prone to worrying about their health and linked this to their use of urgent and emergency services.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Additionally, those aged 18‐44 were more likely to feel overwhelmed when they had an unexpected health problem. 24 These data echo Turnbull et al's findings that young adults more frequently identified themselves as anxious and prone to worrying about their health and linked this to their use of urgent and emergency services. 22 This anxiety and lack of confidence may be an age effect: young adults may be facing unfamiliar symptoms for the first time and be less confident in making independent decisions about their seriousness, and have less familiarity with services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation